[C7H14NO][ClO4]: order–disorder structural change induced sudden switchable dielectric behaviour at room temperature. Issue 44 (31st October 2018) - Fan, Guang-Meng; Gao, Ji-Xing; Shi, Chao; Yu, Hui; Ye, Le; Jiang, Jia-Ying; Shuai, Cijun; Zhang, Yi; Ye, Heng-Yun
Abstract : Static-to-dynamic transition in organic–inorganic hybrid [C7 H14 NO][ClO4 ] exhibits switch-type characteristics during the dielectric transitions between high- and low-dielectric states. Abstract : An organic–inorganic hybrid compound, [ N -oqc]ClO4 (1, N -oqc = N -oxy-quinuclidine cation), was synthesized and characterized. Its structure is defined by the zero-dimensional structure built from the [ N -oqc]ClO4 units from end to end. The crystal structure and dielectric constant measurements reveal that1 undergoes reversible phase transitions at 342/300 K (heating/cooling). The order–disorder motion of [ N -oqc] + and ClO4 − are the origin of the static-to-dynamic transition. Notably, there are sudden dielectric switches between high- and low-dielectric states, making it a new switchable dielectric material.